Diluent and Storage Time Effect on Sperm Abnormality and MDA Level in Muscovy Duck Semen at 27oC - Andaruisworo, Sapta; Tanjungsari, Ardina; Yuniati, Erna; Khairullah, Aswin Rafif (Universitas Airlangga, 2023)
This study aimed to determine sperm abnormality and MDA level in Muscovy duck semen in different dilution and storage at 27oC. This study was used in the level of dilution of glutinous semen with a long time store differently at 27oC. In this study, the parameters of the mass motility of spermatozoa were used individual motility, spermatozoa abnormalities, and activity test. A Muscovy duck, healthy and have a high libido were used then divided into treatment groups i.e. (A0) 0; (A1) 5 times; (A2) 10 times; and (A3) 15 times, the second factor as a subplot was the storage time (BO) 0; (B1) 60 minutes; (B2) 120 minutes; and (B3) 180 minutes stored at 27oC with 3 replications. In results, this study was reported abnormalities at a dilution rate in A1 group of 5 times with a shelf life in B1 group of 60 minutes and in B2 group of 120 minutes.